1996
DOI: 10.3109/10826089609045795
|View full text |Cite
|
Sign up to set email alerts
|

Addicts Drug-Related Dreams: Their Frequency and Relationship to Six-Month Outcomes

Abstract: 101 drug users were interviewed at baseline when 6-weeks abstinent. Eighty-four percent reported having drug-related dreams. More subjects reported drug dreams when abstinent than when using drugs. Ninety percent of subjects were followed-up at 6 months. Higher baseline measures of dream frequency were prospectively related to greater drug use. In the first 7 weeks of follow-up there was a rapid reduction in the number of reports, but half of the sample were still experiencing drug dreams in the sixth month. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 11 publications
1
19
0
8
Order By: Relevance
“…However, it has been observed that frequency of DD significantly abates over longer periods of time (ie, months following treatment; Christo and Franey, 1996;Reid and Simeon, 2001;Yee et al, 2004). Hence, because almost half of the participants stopped using drugs only a few days before recruitment in this study, it seems that DD may be particularly common during early withdrawal from drugs.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, it has been observed that frequency of DD significantly abates over longer periods of time (ie, months following treatment; Christo and Franey, 1996;Reid and Simeon, 2001;Yee et al, 2004). Hence, because almost half of the participants stopped using drugs only a few days before recruitment in this study, it seems that DD may be particularly common during early withdrawal from drugs.…”
Section: Discussionmentioning
confidence: 76%
“…Drug dreams are generally frequent during withdrawal and protracted abstinence (Christo and Franey, 1996;Flowers and Zweben, 1998;Colace, 2014), are mostly reported within the first week of abstinence (Colace, 2004), and can persist for weeks (Hajek and Belcher, 1991), months (Christo and Franey, 1996), and even years (Johnson, 2001) after the cessation of drug use. Although prevalence rates vary from study to study, it has been estimated that more than 85% of individuals experience DDs within 2 months after cessation of drug use (see Colace, 2014 for review).…”
mentioning
confidence: 99%
“…The study of "drug dreams," or the dreams in which drug-addicted patients typically use (or attempt to use) the drugs to which they are Downloaded by [University of Nebraska, Lincoln] at 14:09 03 October 2015 addicted (e.g., Christo & Franey, 1996;Hajek & Belcher, 1991;Johnson, 2001;Yee, Perantie, Dhanani, & Brown, 2004;Persico, 1992;Reid & Simeon, 2001;Steinig, Foraita, Happe, & Heinze, 2011), further show that these dreams are frequently a clear wish-fulfillment or wish-fulfillment attempt (Choi, 1973;Colace, 2000Colace, , 2004aColace, , 2014Colace et al, 2010;Colace, Belsanti, et al, 2014;Denzin, 1988, Fiss, 1980Peters, 2000). Drug dreams suggest an important role of dreams in the regulation of the appetitive and libidinal drives, such as the craving for drugs, in drug addicted patients.…”
Section: The Relevance Of Evidence From "Drug Dreams"mentioning
confidence: 98%
“…They are very short and have a non-ambiguous content. Drug-addicted patients in these dreams generally make use of drugs, or seek and attempt to use them [2,5]. As observed in previous studies, the drug dreams of this patient tended to occur during the early period of abstinence from drugs and are associated with her high craving for cocaine [1,2,5].…”
mentioning
confidence: 71%
“…These drug dreams have been investigated as a prognostic sign and as a clinical tool during the recovery of drug-addicted patients [2,4]. Although studies of dreaming have been undertaken in alcoholic patients and heroin-addicted patients, the literature on dreaming in cocaine addiction remains limited [5].…”
mentioning
confidence: 99%